Compliance with good handling practices among tomato farmers in Kaduna State (2018)
Tomato is one of the most popular fruit vegetables grown in Nigeria because of its nutritional and medicinal value. However, it is highly perishable and large volumes of tomatoes are lost every year due to post harvest handling practices. Good Handling Practices (GHPs) are essential to retain its value which could be lost through microbial contamination and damage. This study therefore examined compliance with GHPs among tomato farmers in Kaduna State. Multi-stage sampling procedure way used to select 150 respondents. Data were obtained through the use of interview schedule and analyzed using Chi-Square and Pearson Product Moment Correlation. The result shows that the mean age of respondents was 52±12 years with majority (96.0%) being males. Respondents produced an average of 1,511 baskets of tomatoes and earned average monthly income of 138,900±47,478. Respondents (90.7%) had high knowledge of GHPs. All the respondents (100%) always handle tomatoes carefully to minimize bruising and breaking of the skin while 92.7% had high compliance with GHPs. The most severe constraint (ẋ=2.00) to compliance was high cost of packaging materials. Type of labour and knowledge were significantly related to compliance with GHPs. Respondents' association should contribute to buy packaging materials in bulk and provision of subsidized packaging equipment like Returnable Plastic Crates (RPC) by the government will encourage farmers to purchase and use in marketing their produce